Rates of MAGE-A3 and PRAME expressing tumors in FFPE tissue specimens from bladder cancer patients: potential targets for antigen-specific cancer immunotherapeutics - Lerut, Evelyne (Int J Clin Exp Pathol, 2015)
Introduction: Antigen-specific active immunotherapy is an investigational therapeutic approach of potential interest for bladder cancer regardless of disease stage. Clinical development of antigen-specific immunotherapeutics against bladder cancer must be preceded by assessment of the expression of relevant genes in bladder tumors. The objectives of this study (NCT01706185) were to assess the rate of expression of the MAGE-A3 and PRAME genes in bladder tumors and to investigate the feasibility of using formalin-fixed paraffin-embedded (FFPE) tumor tissues for testing. Materials and methods: Archived FFPE bladder tumor specimens (any stage) were tested for mRNA expression of MAGE-A3 and PRAME using antigen-specific quantitative reverse transcription polymerase chain reaction assays. Data on patients and tumor characteristics were obtained from hospital records to investigate these characteristics’ possible association with the antigen expression. Results: Over 92% of the 156 tumors examined gave valid antigen test results. Of the tumors with a valid test, 46.5% were MAGE-A3-positive, 32.2% were PRAME-positive and 59.7% positive for at least one of them. Exploratory analyses of possible associations between antigen expression and patient or tumor characteristics did not identify clear associations between antigen expression and any of the variables investigated. Conclusions: Assessment of tumor antigen mRNA expression by using FFPE bladder tissues was feasible. The rates of MAGE-A3-positive and PRAME-positive tumors indicate that both antigens may be interesting targets for immunotherapeutics against bladder cancer.